Review: La relevancia de Carnap: estudio del libro El Programa de Carnap. Ramón Cirera, Andoni Ibarra y Thomas Mormann - Guillermo E. Rosado Haddock (Principia: An International Journal of Epistemology, 2006)
In this critical study of the valuable collection of essays edited by Cirera, Ibarra and Mormann, the present author not only critically assesses the different renderings of Carnap’s writings propounded by the different authors therein represented, but also sketches his own interpretation and subjects to criticism some of the presumed consequences of the demise of logical empiricism.